Central Nervous System Demyelination Related to Tumour Necrosis Factor Alpha Inhibitor. Issue 1 (January 2022) - Chey, Shin Yee; Kermode, Allan G.
Background: An association between tumour necrosis factor alpha (TNF-α) inhibitors exposure and central nervous system (CNS) demyelinating disorders has been postulated but is poorly understood. Objectives: Describe the clinical spectrum and progress of a cohort of patients who developed demyelinating disorder following exposure to TNF-α inhibitor. Methods: Retrospective chart review of patients who presented to a single neurologist in Western Australia between May 2003 and July 2020. Results: 7 patients (6 females and 1 male) were identified. Mean age was 49.1 years. Mean follow-up time was 2.9 years. Mean interval between commencement of TNF-α inhibitor and onset of demyelinating event was 3 years. The spectrum of demyelinating events included transverse myelitis ( N  = 3), acute brainstem syndrome ( N  = 1) and optic neuritis ( N  = 1). 2 patients had an atypical presentation but had MRI findings which unequivocally showed demyelinating changes. 2 patients had a monophasic event while the other 5 patients were diagnosed to have multiple sclerosis. All symptomatic patients with multiple sclerosis were started on disease modifying therapy and remained relapse free during follow-up. Conclusion: Exposure to TNF-α inhibitor appears to increase the risk of demyelinating event. Whether TNFα inhibition directly results in CNS demyelination or trigger demyelination in susceptible individuals requires further research.